The Home Bias in Sovereign Ratings - Fuchs, Andreas; Gehring, Kai (Journal of the European Economic Association, 2017)
Abstract. Using data on 143 sovereigns provided by nine agencies based in six countries, we estimate the determinants of sovereign ratings to test whether agen